2022
DOI: 10.1097/md.0000000000030590
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vedolizumab for inflammatory bowel diseases: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background: Vedolizumab is a humanized monoclonal antibody that inhibits gut-selective α4β7 integrins on the surface of leukocytes, preventing their trafficking into the gastrointestinal tract, and ultimately achieves the effect of suppressing intestinal inflammation. This study aimed to evaluate the efficacy and safety of vedolizumab in the treatment of inflammatory bowel disease.Methods: After a systematic review of relevant studies, the pooled relative risk (RR) and 95% confidence intervals (CIs) were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Treatment goals include inducing clinical remission (ie, induction) and preventing future flares of disease activity (ie, maintenance) . The Table describes the classes of medications used for induction and/or maintenance of UC including dose and administration, efficacy data, and safety considerations. Drugs in different classes have been developed because a number of patients do not respond to drugs and/or lose response over time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment goals include inducing clinical remission (ie, induction) and preventing future flares of disease activity (ie, maintenance) . The Table describes the classes of medications used for induction and/or maintenance of UC including dose and administration, efficacy data, and safety considerations. Drugs in different classes have been developed because a number of patients do not respond to drugs and/or lose response over time.…”
Section: Methodsmentioning
confidence: 99%
“…Vedolizumab adverse events compared with placebo (9 RCTs of UC and Crohn disease (N = 4268): RR, 1.01 (95% CI, 0.96-1.07) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vedolizumab is a selective humanised immunoglobulin G1 monoclonal antibody to α4β7 integrin that blocks lymphocyte trafficking to gut mucosa [ 161 , 162 ]. Both RCTs and observational studies have shown the efficacy of vedolizumab to induce clinical and endoscopic remission in patients who were naïve to, and who previously failed anti-TNF agents [ 163 , 164 ]. Vedolizumab is increasingly used as postoperative prophylactic treatment for CD patients, especially in those at high risk for POR [ 63 ].…”
Section: Biological Agents Other Than Anti-tnfsmentioning
confidence: 99%
“…Inducción y mantenimiento de la respuesta y remisión: Vedolizumab mostró efectividad en términos de respuesta clínica, remisión clínica y curación de la mucosa en la colitis ulcerosa y la enfermedad de Crohn (38).…”
Section: En Generalunclassified